Information Technology Incident Management Planning Using Information Technology Infrastructure Library version 3 at PT Terminal Petikemas Surabaya - Alwi Assegaff; Haryanto Tanuwijaya; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The Information Technology Department of PT Terminal Petikemas Surabaya (TPS) has a Service Desk team that is responsible for handling IT service incidents. Handling of IT service incidents is based on experience, knowledge and agreement. Recurring incidents haven't been handled permanently. It  has an impact on the use of resources in handling incidents.The Solution provide is information technology incident management. Incident management planning as a guidance for handling incident or recovery process of IT services. ITIL v3 as a framework used in developing structured work guidelines for incident management processes. ITIL v3 provides a consistent and repeatable process for restoring IT services.The results of incident management planning as a guide to management work in improving the handling of current incidents. The resulting work guide has been adapted to the internal processes of TPS and ITIL v3, so that it can be used directly as a guide in recording incidents, handling incidents, and resolving IT service incidents.